IMPLEMENTASI BEBERAPA TEORI BELAJAR DALAM APLIKASI SHOLAT FARDHU (Studi: Teori Koneksionisme Edward L. Thorndike, Teori Belajar Medan Kurt Lewin, dan Teori Kondisioning Ivan Pavlop di Masjid Al-Ikhlas Sarirejo) - Wildan Nur Hidayat; Noor Malihah (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
Learning theory is a systematic concept that is scientifically and empirically tested to add insight in overcoming phenomena, especially in learning activities. This study aims to analyze the theory of connectionism, field theory and conditioning theory and their implementation of fardhu prayer. This research method uses qualitative research methods with a literature approach. The qualitative research method is a method based on the disbursement of information related to the implementation of learning theory at the Al-Ikhlas Sarirejo mosque carried out in natural research, searching for data through 1) observation; 2) documentation; and 3) interviews. Researchers also conducted literature study research from primary books and secondary data regarding the three learning theories. Research results: The three major theories have harmony and can be implemented in the practice of fard prayer. 1) Thonrdike with his three pillars of law where the application starts from how the readiness of the students, to the training process that has an impact on whether or not the learning objectives are successful. 2) Lewin argues that individuals can change their environment and vice versa, as evidenced by little priests who are able to attract the attention of other students to learn to be priests; 3) Pavlov, with his theory of conditioning which is in accordance with conceptualized conditioning so that students are accustomed to doing habits and rewards when successfully answering a problem; 3) Pavlov, with his theory of conditioning which is in accordance with conceptualized conditioning.